Factors Affecting Customer Satisfaction with the Quality of Services: Empirical Evidence at da Nang International Airport, Vietnam - Hai, Phan Thanh; Toan, Le Duc; Tam, Vo Viet; Thuong, Mai Thi (Asian Journal of Empirical Research, 2017)
This research is done to measure the factors affecting customer satisfaction with the quality of services of Da Nang International airport. The group of authors uses the method of two-phase mixture with the technique of collecting expert opinions and Structural Equation Modeling (SEM) to analyze quantitative data for the sample including 276 customers who use the services at Da Nang International airport in recent times. Findings show that 06 assessment factors of the quality of services are tangible means, assurance, information, non-aviation services, airline services, utilities. At the same time, these factors affect customer satisfaction at an average level. The group of authors, based on these results, offers some suggestions for managers in perfecting some policies and specifies the suggestions, limitations for the next research.